Consensus Statement of the IAP - Neurodevelopmental Chapter On Neurodevelopmental Disorders Habilitation Process: Strategic Plan for Prevention, Early Detection and Early Intervention - Nair, M. K. C.; Ahmed, Shabina; Multani, Kawaljit Singh; Ismail, P. M. Mohamed; Kamath, S. S.; Dalwai, Samir H.; Meenai, Zafar; Suman, Praveen; Seth, Shambhavi; Srivastava, Leena; Srinivasan, Roopa; Lewin, Maria; et al. (Indian pediatrics, 2024)
Justification Neurodevelopmental disorders, as per DSM-V, are described as a group of conditions with onset in the development period of childhood. There is a need to distinguish the process of habilitation and rehabilitation, especially in a developing country like India, and define the roles of all stakeholders to reduce the burden of neurodevelopmental disorders. Process Subject experts and members of Indian Academy of Pediatrics (IAP) Chapter of Neurodevelopmental Pediatrics, who reviewed the literature on the topic, developed key questions and prepared the first draft on guidelines. The guidelines were then discussed by the whole group through online meetings, and the contentious issues were discussed until a general consensus was arrived at. Following this, the final guidelines were drafted by the writing group and approved by all contributors. Objectives These guidelines aim to provide practical clinical guidelines for pediatricians on the prevention, early diagnosis and management of neurodevelopmental disorders (NDDs) in the Indian settings. It also defines the roles of developmental pediatricians and development nurse counselor. Statement There is a need for nationwide studies with representative sampling on epidemiology of babies with early NDD in the first 1000 days in India. Specific learning disability (SLD) has been documented as the most common NDD after 6 years in India, and special efforts should be made to establish the epidemiology of infants and toddlers at risk for SLD, where ever measures are available. Preconception counseling as part of focusing on first 1000 days; Promoting efforts to organize systematic training programs in Newborn Resuscitation Program (NRP); Lactation management; Developmental follow-up and Early stimulation for SNCU/NICU graduates; Risk stratification of NICU graduates, Newborn Screening; Counseling parents; Screening for developmental delay by trained professionals using simple validated Indian screening tools at 4, 8, 12, 18 and 24 months; Holistic assessment of 10 NDDs at child developmental clinics (CDCs)/district early intervention centre (DEICs) by multidisciplinary team members; Confirmation of diagnosis by developmental pediatrician/developmental neurologist/child psychiatrist using clinical/diagnostic tools; Providing parent guided low intensity multimodal therapies before 3 years age as a center-based or home-based or community-based rehabilitation; Developmental pediatrician to seek guidance of pediatric neurologist, geneticist, child psychiatrist, physiatrist, and other specialists, when necessary; and Need to promote ongoing academic programs in clinical child development for capacity building of community based therapies, are the chief recommendations.